Investigation on the Characteristics of Biodiesel Droplets in the Engine Cylinder - Ali Raza; Hassan Mehboob; Sajjad Miran; Waseem Arif; Syed Farukh Javaid Rizvi (Energies, 2020)
The world is moving towards renewable energy sources rapidly and, at present, fossil fuels are reducing day by day. In this scenario, biofuels have become an attractive alternative to conventional diesel fuels. In the present work, the vaporization of Thumba biodiesel is numerically modeled using the finite volume-based approach in ANSYS Fluent and the results are compared with diesel fuel. Evaporation of fuels is governed by the conservation equations of energy, momentum, and mass. Owing to high temperature and pressure conditions, turbulence is present in the engine cylinder. To account for the turbulence effects, the Reynolds-averaged Navier–Stokes (RANS) turbulence model is used. Heat transfer to droplet and mass lost by the droplets is governed by the discrete phase model equations. The obtained results include the droplet lifetime, increase in temperature of a droplet, and velocity profiles. It is observed that the size and temperature of fuel droplets and ambient temperature have a significant effect on the evaporation time of fuel droplets in the engine cylinder. By reducing the droplet size, the complete evaporation of fuels can be achieved. Droplets having a high temperature have a short evaporation time and high evaporation rate. It is noted that, at a higher temperature, biodiesel evaporates more quickly than diesel fuel, thus producing complete combustion and hence giving maximum power output.